Porous IrRu oxide catalyst, preparation method and catalytic application

By using non -ionic surfactants as soft templates, prepare a porous IRRU oxide catalyst with high activity and high stability, solve the problem of low activity and stability of IR and RU base catalysts, and realizes various types in various types. Outstanding performance in catalytic applications.

CN118949976BActive Publication Date: 2025-01-28TIANJIN UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411433090.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-28
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

Ir-based and Ru-based catalysts have low activity and insufficient stability in organic synthesis, catalytic combustion, electrocatalysis and battery technologies, making it difficult to have high activity and high stability at the same time.

Method used

The non -ionic surfactant is used as a soft template, and the porous IRRU oxide catalyst is prepared by the soft template legal system, and the nanoparticle catalyst with a porous structure is formed by drying and burning treatment.

Benefits of technology

It improves the activity and stability of porous IRRU oxide catalysts, and enhances its catalytic capabilities in biomass oxidation reactions and oxygen reactions, especially in the field of low temperature biomass transformation and electrolytic water technology fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118949976B_ABST
    Figure CN118949976B_ABST
Patent Text Reader

Abstract

The present invention provides a porous IrRu oxide catalyst, a preparation method and a catalytic application, and belongs to the technical field of precious metal oxide catalysts. The preparation method of the IrRu oxide catalyst comprises: adding an iridium salt precursor and a ruthenium salt precursor to an acidic solution containing a non-ionic surfactant and stirring to obtain a mixed solution; drying the mixed solution to obtain a gel adsorbed with iridium ions and ruthenium ions; calcining the gel adsorbed with iridium ions and ruthenium ions in air to prepare a porous IrRu oxide catalyst. The non-ionic surfactant forms micelles by interacting with water molecules in an acidic solvent; the acidic environment helps dissolve the iridium salt precursor and the ruthenium salt precursor and reduces their hydrolysis and precipitation. The present invention facilitates the subsequent calcination to form a catalyst with porous properties by forming stable micelles, thereby forming more active sites.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of precious metal oxide catalysts, and in particular to a porous IrRu oxide catalyst, a preparation method and catalytic application. Background Art

[0002] Ir-based and Ru-based catalysts are mostly used in organic synthesis, catalytic combustion, electrocatalysis and battery technology, but they have low activity and insufficient stability. It is difficult for Ir-based and Ru-based catalysts to have both high activity and high stability. At the same time, since Ir-based and Ru-based catalysts are precious metal catalysts, their activity per unit mass is also difficult to be effectively improved. Summary of the invention

[0003] In view of this, in order to at least partially solve at least one of the above-mentioned technical problems, the present invention provides a porous IrRu oxide catalyst, a preparation method and a catalytic application.

[0004] According to an embodiment of one aspect of the present invention, a porous IrRu oxide catalyst is provided, wherein the weight percentage content of iridium in the porous IrRu oxide catalyst is 1-100%.

[0005] According to another embodiment of the present invention, there is provided a catalytic application of the porous IrRu oxide catalyst as described above in biomass oxidation reaction and oxygen evolution reaction.

[0006] According to another embodiment of the present invention, a method for preparing a porous IrRu oxide catalyst is provided, comprising: adding an iridium salt precursor and a ruthenium salt precursor to an acidic solution containing a non-ionic surfactant and stirring to obtain a mixed solution, wherein the iridium ions and the ruthenium ions are adsorbed onto micelles formed by the non-ionic surfactant; drying the mixed solution to obtain a gel adsorbed with the iridium ions and the ruthenium ions; and calcining the gel adsorbed with the iridium ions and the ruthenium ions in air to obtain a porous IrRu oxide catalyst.

[0007] According to an embodiment of the present invention, the nonionic surfactant is a polyether nonionic surfactant.

[0008] According to an embodiment of the present invention, the non-ionic surfactant is selected from any one or more of polyether F68, polyether F123, polyether F124, polyether F127, polyether F188, polyether L65, polyethylene glycol-b-polystyrene (PEO-b-PS), poly(propylene glycol)-block-poly(ethylene glycol)-block-poly(propylene glycol), fatty alcohol polyoxyethylene ether, fatty acid polyoxyethylene ester, octadecylamine polyoxyethylene ether, and polyoxyethylene fatty amide 704.

[0009] According to an embodiment of the present invention, an acidic solution containing a nonionic surfactant is prepared by the following operations: dissolving a nonionic surfactant in water and stirring to obtain a solution containing a nonionic surfactant; adding an acid to the solution to form an acidic solution containing a nonionic surfactant; wherein the acid includes a combination of hydrochloric acid, glacial acetic acid, formic acid, nitric acid, and sulfuric acid, preferably a combination of hydrochloric acid and glacial acetic acid.

[0010] According to an embodiment of the present invention, the solvent used to form the acidic solution is at least one of water, tetrahydrofuran, anhydrous ethanol, and isopropanol, preferably water.

[0011] According to an embodiment of the present invention, the drying temperature is 20-90°C; the calcination conditions are: heating to 50-1000°C at a heating rate of 1-100°C / min, and calcining at a heat treatment temperature of 50-1000°C for 0.1-50h.

[0012] Preferably, the calcination treatment conditions are: heating to 200-800° C. at a heating rate of 1-20° C. / min, and calcining at a heat treatment temperature of 200-800° C. for 0.5-10 h.

[0013] According to an embodiment of the present invention, the iridium salt precursor includes: at least one of iridium tetrachloride, iridium trichloride or its hydrate, chloroiridic acid or its hydrate, iridium acetate, ammonium chloroiridate, potassium chloroiridate, sodium chloroiridate, potassium bromoiridate, sodium bromoiridate, tricarbonyl iridium chloride, tetrairidium dodecacarbonyl, and iridium iodide; the ruthenium salt precursor includes: at least one of ruthenium trichloride or its hydrate, ammonium chlororuthenate, potassium chlororuthenate, sodium chlororuthenate, ruthenium acetylacetonate, ruthenium acetate, ruthenium acetate, ruthenium bromide, ruthenium iodide, potassium perruthenate, ruthenium hexacarbonyl chloride, triruthenium dodecacarbonyl, ruthenium red tetrahydrate, and ruthenium nitrosyl acetate.

[0014] According to an embodiment of the present invention, other precious metal precursors are optionally added during the preparation process, including at least one of chloroplatinic acid, ammonium chloroplatinate, platinum dichloride, platinum sulfite, platinum tetrachloride, potassium chloroplatinate, potassium chloroplatinite, lithium chloroplatinate hydrate, sodium chloroplatinite, sodium chloroplatinate, potassium platinum hexabromide, chloroauric acid, potassium gold chloride, sodium chloroaurate, palladium chloride, sodium chloropalladate, ammonium chloropalladate, palladium nitrate, palladium sulfate, palladium propionate, potassium bromopalladate, potassium chloropalladate, palladium acetate, sodium hexachloropalladate, rhodium chloride, potassium chlororhodate, ammonium chlororhodate, rhodium nitrate, rhodium sulfate, and rhodium acetate.

[0015] According to another embodiment of the present invention, there is provided a proton exchange membrane, comprising a membrane substrate and a first catalyst layer, wherein the first catalyst layer is formed on a first surface of the membrane substrate, and the first catalyst layer comprises the porous IrRu oxide catalyst as described above.

[0016] Based on the above technical solution, a porous IrRu oxide catalyst, a preparation method and a catalytic application of the present invention have at least one or part of the following beneficial effects:

[0017] According to an embodiment of the present invention, a porous IrRu composite oxide catalyst with high activity and high stability was prepared by using a non-ionic surfactant-assisted soft template method, and was successfully applied to low-temperature biomass conversion and oxygen evolution reaction.

[0018] According to an embodiment of the present invention, by immersing a nonionic surfactant in an acidic solution, the hydrophilic polar head on the nonionic surfactant faces outward, and hydrogen bonds or other forms of interactions are formed with water molecules in the acidic solution; the hydrophobic hydrocarbon chain faces inward, and self-assembles to form a stable micelle structure. The polar head of the nonionic surfactant is uncharged, and there is no functional group that can release or absorb protons, so the nonionic surfactant does not form charged ions in water. Furthermore, since it does not form ions, the solubility and micelle formation of the nonionic surfactant are not affected by the pH value of the solution. The micelles formed by nonionic surfactants in water are mainly maintained stable by hydrophobic interactions (interactions between hydrophobic chains) and hydrophilic interactions (interactions between polar heads and water molecules). These interactions are independent of pH, so the micelles can maintain a relatively stable state in a wide pH range, which helps to adsorb iridium ions and ruthenium ions in an acidic environment to form stable Ir 3+ / Ru 3+ The micellar assembly is beneficial to improve the stability of the preparation process. By using a non-ionic surfactant as a soft template, the present invention eliminates the complicated steps of synthesizing a hard template and removing the hard template compared to the hard template method, greatly simplifies the material preparation operation, and is beneficial to subsequent macro-scale preparation. In addition, the use of a non-ionic surfactant to form micelles and then calcining in air helps to form a porous IrRu oxide catalyst, which is beneficial to expose and form more active sites. The porous IrRu oxide catalyst is a nanoparticle. When subsequently applied to biomass oxidation reactions, the porous IrRu oxide catalyst has good catalytic ability. When subsequently applied to the field of water electrolysis technology, the porous IrRu oxide catalyst is used as a water electrolysis anode, which is beneficial to promote the oxygen evolution reaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The above and other objects, features and advantages of the present invention will become more apparent through the following description of the embodiments of the present invention with reference to the accompanying drawings, in which:

[0020] Figure 1 A flow chart showing a method for preparing a porous IrRu oxide catalyst according to an embodiment of the present invention;

[0021] Figure 2a The scanning electron microscope (SEM) image of the IrRu oxide catalyst 1 prepared in Example 1 of the present invention at a magnification of 500 nm is shown;

[0022] Figure 2b is with Figure 2a SEM images of IrRu oxide catalyst 1 at different positions at the same magnification;

[0023] Figure 2c The SEM image of the IrRu oxide catalyst 1 prepared in Example 1 of the present invention at a magnification of 1 μm is shown;

[0024] Figure 2d is with Figure 2c SEM images of IrRu oxide catalyst 1 at different positions at the same magnification;

[0025] Figure 3 The transmission electron microscope (TEM) image of the IrRu oxide catalyst 1 prepared in Example 1 of the present invention at a magnification of 1 μm is shown;

[0026] Figure 4 The X-ray diffraction spectrum (XRD) of the IrRu oxide catalyst 1 prepared in Example 1 of the present invention is shown;

[0027] Figure 5 The cyclic voltammetry (CV) stability curve of the IrRu oxide catalyst 1 prepared in Example 1 of the present invention is shown;

[0028] Figure 6 The linear voltammetric scanning (LSV) histograms after iR compensation of the oxide catalysts prepared in Examples 1 to 5 of the present invention and the IrRu oxide catalyst 1' prepared in Comparative Example 1 are shown. DETAILED DESCRIPTION

[0029] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments and with reference to the accompanying drawings.

[0030] But it should be understood that these descriptions are exemplary only, and are not intended to limit the scope of the present invention. In the following detailed description, for ease of explanation, many specific details are set forth to provide a comprehensive understanding of embodiments of the present invention. However, it is apparent that one or more embodiments may also be implemented without these specific details. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of concepts of the present invention.

[0031] The terms used herein are only for describing specific embodiments and are not intended to limit the present invention. The term "comprising" used herein indicates the existence of features, steps, operations, but does not exclude the existence or addition of one or more other features.

[0032] In the case of using expressions such as "at least one of A, B, and C, etc.", it should generally be interpreted in accordance with the meaning of the expression generally understood by those skilled in the art (for example, "a system having at least one of A, B, and C" should include but is not limited to a system having A alone, B alone, C alone, A and B, A and C, B and C, and / or A, B, C, etc.). In the case of using expressions such as "at least one of A, B, or C, etc.", it should generally be interpreted in accordance with the meaning of the expression generally understood by those skilled in the art (for example, "a system having at least one of A, B, or C" should include but is not limited to a system having A alone, B alone, C alone, A and B, A and C, B and C, and / or A, B, C, etc.).

[0033] All terms (including technical and scientific terms) used herein have the meanings commonly understood by those skilled in the art unless otherwise defined. It should be noted that the terms used herein should be interpreted as having a meaning consistent with the context of this specification and should not be interpreted in an idealized or overly rigid manner.

[0034] It should be noted that the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or device including the element.

[0035] In related technologies, hydrogen energy is often used to replace fossil energy as a sustainable fuel. Water electrolysis is an important way to produce hydrogen energy, but in the water electrolysis reaction, the oxygen evolution reaction kinetics of the anode is relatively slow, making the efficiency of water electrolysis hydrogen production low.

[0036] In the process of realizing the concept of the present invention, it is found that by immersing the non-ionic surfactant in water of an acidic solution, the hydrophilic polar head on the non-ionic surfactant faces outward, forming an interaction with water molecules; and the hydrophobic hydrocarbon chain on the non-ionic surfactant faces inward, thereby forming a stable micelle structure. And the micelles formed by the non-ionic surfactant are maintained in a stable state by hydrophilic-hydrophobic interactions, therefore, they are not affected by pH values, and the stability of the IrRu oxide preparation process is improved. During subsequent calcination in air, due to the supporting effect of the micelles, it helps to form IrRu oxide catalyst nanoparticles with a porous structure, which can expose more active sites.

[0037] Figure 1 A flow chart of a method for preparing a porous IrRu oxide catalyst according to an embodiment of the present invention is shown.

[0038] Specifically, according to an embodiment of one aspect of the present invention, a method for preparing a porous IrRu oxide catalyst is provided. Figure 1 , including steps S101~S103.

[0039] In step S101, an iridium salt precursor and a ruthenium salt precursor are added to an acidic solution containing a nonionic surfactant and stirred to obtain a mixed solution, wherein iridium ions and ruthenium ions are adsorbed onto micelles formed by the nonionic surfactant.

[0040] According to an embodiment of the present invention, the nonionic surfactant is generally composed of a hydrophilic polar head and a plurality of hydrophobic hydrocarbon chains, and the polar head of the nonionic surfactant has no charge.

[0041] In step S102, the mixed solution is dried to obtain a gel adsorbing iridium ions and ruthenium ions.

[0042] According to an embodiment of the present invention, after the mixed solution containing micelles is dried, a gel with elasticity and network structure can be obtained. The reason is that after removing water, the interaction between non-ionic surfactants leads to the formation of solid or semi-solid forms. In addition, during the drying process, non-ionic surfactants may also self-assemble or crystallize. Iridium ions and ruthenium ions are evenly dispersed on micelles and converted into a gel state after drying. The gel state has a high specific surface area and porous structure, can provide a large number of adsorption sites, and can provide a highly dispersed support environment for iridium ions and ruthenium ions. Drying helps to maintain the porous structure of the gel.

[0043] In step S103, the gel adsorbed with iridium ions and ruthenium ions is calcined in air to prepare a porous IrRu oxide catalyst.

[0044] According to an embodiment of the present invention, during the calcination process in air, the increase in temperature causes the organic components in the gel to decompose and burn, so that the iridium ions and ruthenium ions are oxidized and converted into corresponding iridium oxides and ruthenium oxides. And as the template is oxidized to carbon dioxide at high temperature, a nanostructure is formed. Iridium oxide and ruthenium oxide have catalytic activity and are formed in the nanostructure with a high active site exposure rate.

[0045] According to an embodiment of the present invention, by immersing a nonionic surfactant in an acidic solution, the hydrophilic polar head on the nonionic surfactant faces outward, and hydrogen bonds or other forms of interactions are formed with water molecules in the acidic solution; the hydrophobic hydrocarbon chain faces inward, and self-assembles to form a stable micelle structure. The polar head of the nonionic surfactant is uncharged, and there is no functional group that can release or absorb protons, so the nonionic surfactant does not form charged ions in water. Furthermore, since it does not form ions, the solubility and micelle formation of the nonionic surfactant are not affected by the pH value of the solution. The micelles formed by the nonionic surfactant in water are mainly maintained stable by hydrophobic interactions (interactions between hydrophobic chains) and hydrophilic interactions (interactions between polar heads and water molecules). These interactions are independent of the pH value, so the stability of the micelles can remain relatively stable over a wide pH range. It helps to adsorb iridium ions and ruthenium ions to form stable Ir 3+ / Ru 3+ The micellar assembly is beneficial to improve the stability of the preparation process. By using a non-ionic surfactant as a soft template, the present invention omits the complicated steps of synthesizing a hard template and removing the hard template compared to the hard template method, greatly simplifies the material preparation operation, and is beneficial to the subsequent macro-preparation. In addition, the use of a non-ionic surfactant to form micelles and then calcining in air to form a catalyst with a porous structure is beneficial to expose more active sites, and has better catalytic ability when subsequently applied to biomass oxidation reactions; when applied to proton exchange membranes, it can be used as an anode for water electrolysis to promote the oxygen evolution reaction.

[0046] According to an embodiment of the present invention, an iridium salt precursor and a ruthenium salt precursor are added to an acidic solution containing a non-ionic surfactant and stirred. The purpose of using the acidic solution is to promote the dissolution of the iridium salt precursor and / or the ruthenium salt precursor and prevent the premature precipitation and hydrolysis of iridium ions and ruthenium ions, which is conducive to promoting the adsorption of iridium ions and ruthenium ions onto micelles.

[0047] According to an embodiment of the present invention, the nonionic surfactant is a polyether nonionic surfactant. The polyether nonionic surfactant has a hydrophilic group that does not ionize, such as an ether bond, a polyoxyethylene chain, etc., and therefore, does not cause precipitation or aggregation of iridium ions and ruthenium ions, and helps to maintain the stable adsorption state of iridium ions and ruthenium ions. In addition, the polyether nonionic surfactant maintains a balanced state of hydrophilicity and hydrophobicity in its molecular structure, which is conducive to forming a more uniform dispersion system in water, and is conducive to maintaining the stable adsorption state of iridium ions and ruthenium ions.

[0048] Preferably, the nonionic surfactant is selected from any one or more of polyether F68, polyether F123, polyether F124, polyether F127, polyether F188, polyether L65, polyethylene glycol-b-polystyrene (PEO-b-PS), poly(propylene glycol)-block-poly(ethylene glycol)-block-poly(propylene glycol), fatty alcohol polyoxyethylene ether, fatty acid polyoxyethylene ester, octadecylamine polyoxyethylene ether, and polyoxyethylene fatty amide 704. In the process of conducting the relevant experiments of the present invention, it was found that when the above nonionic surfactant was used, the prepared porous IrRu oxide catalyst was more stable and had better catalytic performance.

[0049] According to an embodiment of the present invention, the solvent used to form the acidic solution is at least one of water, tetrahydrofuran, anhydrous ethanol, and isopropanol, preferably water. When the solvent used to form the acidic solution is tetrahydrofuran, anhydrous ethanol or isopropanol, it can dissolve the iridium salt precursor, the ruthenium salt precursor and the non-ionic surfactant, and can ensure the uniformity of the mixed solution. When the non-ionic surfactant is in the above-mentioned solvent, the hydrophobic hydrocarbon chain faces outward and the hydrophilic polar head faces inward, thereby self-assembling to form a relatively stable reverse micelle structure. As a result, the reverse micelles formed by the non-ionic surfactant in the solvent are also maintained in a stable state through hydrophobic interactions (interactions between hydrophobic chains and solvents) and hydrophilic interactions (interactions between polar hydrophilic ends). These interactions are independent of pH value. Therefore, the reverse micelles can also maintain a relatively stable state under a wide pH range, which is helpful to adsorb iridium ions and ruthenium ions in an acidic environment to form stable Ir 3+ / Ru 3+ The micellar assembly is beneficial to improving the stability of the preparation process.

[0050] According to an embodiment of the present invention, an acidic solution containing a nonionic surfactant is prepared by the following operations: dissolving a nonionic surfactant in water and stirring to obtain a solution containing a nonionic surfactant; adding an acid to the solution to form an acidic solution containing a nonionic surfactant; wherein the acid comprises a combination of hydrochloric acid, glacial acetic acid, formic acid, nitric acid, and sulfuric acid. Preferably, the acid is a combination of hydrochloric acid and glacial acetic acid. Firstly dissolving the nonionic surfactant in water is conducive to the formation of sufficient interaction between the nonionic surfactant and water molecules, thereby forming a relatively stable micelle structure. A combination of hydrochloric acid and glacial acetic acid is added to adjust to an acidic solution, wherein hydrochloric acid is a stronger acid that can reduce the pH value of the solution more quickly, and glacial acetic acid is a relatively weak acid that can further adjust the pH value of the solution. Such an acidic environment helps to keep iridium ions and ruthenium ions stable in the solution, and prevents premature hydrolysis and precipitation of iridium ions and ruthenium ions. The ions in hydrochloric acid and acetic acid can form complexes with iridium ions and ruthenium ions, thereby further stabilizing iridium ions and ruthenium ions and reducing their reaction with water molecules. Adding hydrochloric acid and acetic acid can increase the ionic strength in the solution and help reduce the hydrolysis tendency of iridium ions and ruthenium ions.

[0051] Specifically, 0.5-2 g of a nonionic surfactant, for example, 0.5 g, 1 g, 1.5 g or 2 g, is dissolved in 30 mL of water and stirred for 10 min to 1 h to form a solution, for example, 10 min, 20 min, 0.5 h, 0.7 h, 0.8 h or 1 h. 0.5-4 mL of hydrochloric acid and 0.5-4 mL of glacial acetic acid are added to the above solution, for example, 2.4 mL of hydrochloric acid and 1.4 mL of glacial acetic acid, 4 mL of hydrochloric acid and 1 mL of glacial acetic acid, 0.5 mL of hydrochloric acid and 4 mL of glacial acetic acid, 4 mL of hydrochloric acid and 0.5 mL of glacial acetic acid or 2 mL of hydrochloric acid and 2 mL of glacial acetic acid, and stirred evenly to form an acidic solution. 0.1-10 mmol of iridium salt precursor and ruthenium salt precursor are added to the acidic solution, for example, 0.3 mmol of iridium salt precursor and 0.1 mmol of ruthenium salt precursor, 0.2 mmol of iridium salt precursor and 0.2 mmol of ruthenium salt precursor, 0.1 mmol of iridium salt precursor and 0.3 mmol of ruthenium salt precursor, 0.0.1 mmol of iridium salt precursor and 10 mmol of ruthenium salt precursor, 10 mmol of iridium salt precursor and 0.1 mmol of ruthenium salt precursor, etc. can be added, but not limited thereto. Then, a drying treatment is performed to form a gel, and after the gel is formed, it is calcined in air to remove the non-ionic surfactant, which is a soft template.

[0052] According to an embodiment of the present invention, the drying process may be, for example, drying in a blast drying oven or rotary evaporation. The temperature of the blast drying oven is 30 to 90°C, for example, 30°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C or 90°C, preferably 50°C. The temperature of the rotary evaporation is 20 to 90°C, for example, 20°C, 30°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C or 90°C, preferably 50°C. The conditions for the calcination process are: heating to 50 to 1000°C at a heating rate of 1 to 100°C / min, and calcining at a heat treatment temperature of 50 to 1000°C for 0.1 to 50h.

[0053] Preferably, the calcination treatment conditions are: heating to 200-800°C at a heating rate of 1-20°C / min, the heating rate can be, for example, 1°C / min, 5°C / min, 10°C / min, 15°C / min or 20°C / min, and heating to 200°C, 300°C, 400°C, 500°C, 600°C, 700°C or 800°C. Calcination at a heat treatment temperature of 200-800°C for 0.5-10h, for example, 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h or 10h.

[0054] According to an embodiment of the present invention, the iridium salt precursor includes: at least one of iridium tetrachloride, iridium trichloride or its hydrate, chloroiridic acid or its hydrate, iridium acetate, ammonium chloroiridate, potassium chloroiridate, sodium chloroiridate, potassium bromoiridate, sodium bromoiridate, tricarbonyl iridium chloride, tetrairidium dodecacarbonyl, and iridium iodide; the ruthenium salt precursor includes: at least one of ruthenium trichloride or its hydrate, ammonium chlororuthenate, potassium chlororuthenate, sodium chlororuthenate, ruthenium acetylacetonate, ruthenium acetate, ruthenium acetate, ruthenium bromide, ruthenium iodide, potassium perruthenate, ruthenium hexacarbonyl chloride, triruthenium dodecacarbonyl, ruthenium red tetrahydrate, and ruthenium nitrosyl acetate. The above-mentioned iridium salt precursor and ruthenium salt precursor have good solubility, which helps to improve the uniformity of their adsorption on micelles, control the reaction of the precursors in nanoscale micropores or interlayer gaps, and help to form IrRu oxide nanoparticles with a porous structure after calcination, thereby increasing the active sites of their catalytic reactions.

[0055] According to an embodiment of the present invention, other precious metal precursors are optionally added in the preparation process, that is, they can be added or not added according to the selection, including at least one of chloroplatinic acid, ammonium chloroplatinate, platinum dichloride, platinum sulfite, platinum tetrachloride, potassium chloroplatinate, potassium chloroplatinite, lithium chloroplatinate hydrate, sodium chloroplatinite, sodium chloroplatinate, potassium platinum hexabromide, chloroauric acid, potassium gold chloride, sodium chloroaurate, palladium chloride, sodium chloropalladate, ammonium chloropalladate, palladium nitrate, palladium sulfate, palladium propionate, potassium bromopalladate, potassium chloropalladate, palladium acetate, sodium hexachloropalladate, rhodium chloride, potassium chlororhodate, ammonium chlororhodate, rhodium nitrate, rhodium sulfate, and rhodium acetate.

[0056] According to an embodiment of the present invention, the molar ratio of the iridium salt precursor to the ruthenium salt precursor is 0-1:1-0. For example, it can be 0:1, 1:0, 1:1, but it is not limited thereto.

[0057] According to another embodiment of the present invention, a porous IrRu oxide catalyst is provided, which is prepared by the method as described above.

[0058] According to an embodiment of the present invention, the porous IrRu oxide catalyst prepared by the above method has a relatively stable nanostructure, and when subsequently applied to a biomass oxidation reaction, the porous IrRu oxide catalyst has good catalytic ability. When subsequently applied to the field of water electrolysis technology, it has more IrRu oxide catalytic active sites, which helps to promote the oxygen evolution reaction.

[0059] According to an embodiment of the present invention, in the porous IrRu oxide catalyst, the weight percentage content of iridium is 1 to 100%, for example, it can be 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80% or 90%, preferably 10 to 90%. Iridium oxide has high activity. By doping iridium oxide in the IrRu oxide catalyst, the electronic structure of the catalyst surface is changed, the energy band structure can be optimized, which is conducive to improving the electron transfer efficiency and the kinetic performance of the catalytic reaction. The doping of iridium oxide helps to form more active sites. The addition of iridium oxide can inhibit the excessive oxidation and dissolution of ruthenium, and maintain the stability of the porous IrRu oxide catalyst and the reliability of long-term use.

[0060] According to another embodiment of the present invention, there is provided a catalytic application of the porous IrRu oxide catalyst as described above in biomass oxidation reaction and oxygen evolution reaction.

[0061] According to an embodiment of the present invention, the porous IrRu oxide catalyst has good catalytic ability when applied to biomass oxidation reaction, and can catalyze the oxidation reaction. It is applied in oxygen evolution reaction, for example, it can be proton exchange membrane water electrolysis. It can support higher current density, which is conducive to improving the hydrogen production efficiency of the electrolytic cell, and can effectively improve the performance of the proton exchange membrane water electrolysis cell, and promote its application in the field of hydrogen energy preparation and energy storage.

[0062] According to an embodiment of another aspect of the present invention, there is provided a proton exchange membrane, comprising a membrane substrate and a first catalyst layer, wherein the first catalyst layer is formed on a first surface of the membrane substrate, and the first catalyst layer comprises a porous IrRu oxide catalyst as described above. The porous IrRu oxide catalyst has relatively excellent catalytic activity, which is beneficial to reducing the overpotential of the oxygen evolution reaction, thereby improving the overall energy conversion efficiency; the porous IrRu oxide catalyst has high stability in an acidic environment, and can operate stably for a long time in proton exchange membrane water electrolysis; the durability of the porous IrRu oxide catalyst in a strong oxidizing environment is better than that of a single metal catalyst, which is beneficial to extending the service life of the electrolytic cell. The porous IrRu oxide catalyst has oxygen vacancies or defects, which is beneficial to the transfer of electrons, thereby enhancing the electrocatalytic activity of the oxygen evolution reaction.

[0063] According to an embodiment of the present invention, the proton exchange membrane includes one of a perfluorosulfonic acid membrane, a partially fluorinated polymer membrane, a novel non-fluorinated polymer membrane, and a composite proton exchange membrane.

[0064] According to an embodiment of the present invention, the proton exchange membrane of the present invention further comprises a second catalyst layer formed on a second surface of the membrane substrate opposite to the first surface. The second catalyst layer may use a hydrogen evolution catalyst, such as a Pt / C catalyst, but is not limited thereto.

[0065] The present invention is further described below by examples, drawings and related test experiments and results thereof. In the detailed description below, for ease of explanation, many specific details are set forth to provide a comprehensive understanding of the embodiments of the present invention. However, it is obvious that one or more embodiments may also be implemented without these specific details. And, in the absence of conflict, the details in the following embodiments may be combined arbitrarily into other feasible embodiments.

[0066] It should be noted that the following specific examples are only for illustration, and the protection scope of the present invention is not limited thereto. The chemicals and raw materials used in the following examples are all commercially available or homemade by recognized processing methods.

[0067] Embodiment 1:

[0068] 1.6 g of nonionic surfactant polyether F188 was dissolved in 30 mL of water and stirred for 0.5 h to form a solution.

[0069] Then, 2.4 mL of concentrated hydrochloric acid and 1.4 mL of glacial acetic acid were added to the solution and stirred evenly, and 0.3 mmol of IrCl3·3H2O and 0.1 mmol of RuCl3·3H2O were added and stirred evenly to allow the iridium salt precursor and the ruthenium salt precursor to be adsorbed onto the F188 micelles.

[0070] The formed solution was placed in an oven at 50°C and slowly dried until a gel was obtained, and the obtained gel was calcined in air at 500°C for 4 hours to prepare IrRu oxide catalyst 1. Energy dispersive X-ray spectroscopy (EDX) analysis showed that the weight ratio of Ir:Ru in IrRu oxide catalyst 1 was about 4.8:1.

[0071] Figure 2a The SEM image of the IrRu oxide catalyst 1 prepared in Example 1 of the present invention at a magnification of 500 nm is shown; Figure 2b is with Figure 2a SEM images of IrRu oxide catalyst 1 at different positions at the same magnification; Figure 2c The SEM image of the IrRu oxide catalyst 1 prepared in Example 1 of the present invention at a magnification of 1 μm is shown; Figure 2d is with Figure 2c SEM images of IrRu oxide catalyst 1 at different positions at the same magnification. Figure 2a~Figure 2d As shown, it can be seen that the IrRu oxide catalyst 1 has a porous structure and is a nanoparticle.

[0072] Figure 3 The TEM image of the IrRu oxide catalyst 1 prepared in Example 1 of the present invention at a magnification of 1 μm is shown. Figure 2a~Figure 2d as well as Figure 3 It can be seen from the combination that the prepared IrRu oxide catalyst 1 is a porous structure formed by the accumulation of nanoparticles, which helps to increase the specific surface area of ​​the IrRu oxide catalyst 1 and provide a larger number of catalytic active sites. It can effectively enhance the catalytic activity of the IrRu oxide catalyst 1 in biomass oxidation reactions, and can also enhance the oxygen evolution reaction activity when used in the anode of water electrolysis.

[0073] Figure 4 FIG. 1 shows the XRD pattern of the IrRu oxide catalyst 1 prepared in Example 1 of the present invention. Figure 4 As shown, it can be seen from the XRD pattern that the IrRu oxide catalyst 1 is a composite of rutile phase IrO2 (PDF#15-0870) and RuO2 (PDF#65-2824), confirming the specific structure of the IrRu oxide catalyst 1.

[0074] The IrRu oxide material 1 prepared in Example 1 was subjected to a catalytic test:

[0075] IrRu oxide catalyst 1 and xylose were added to an alkaline solution, and under the catalytic action, xylose was oxidized to lactic acid. The reaction temperature was 60°C, and the alkaline solution used was a 3M KOH solution. After the reaction, the xylose conversion rate was 95.51%, and the lactic acid yield was 55.39%, indicating that IrRu oxide catalyst 1 has good catalytic ability in the catalytic oxidation reaction of biomass.

[0076] The IrRu oxide catalyst 1 prepared in Example 1 was subjected to a proton exchange membrane water electrolysis test: at 80°C, the current density was 1 A / cm 2 When the voltage is 1.85V, 2A / cm 2 The voltage at the current density was 2.12 V, indicating that catalyst 1 has good application potential.

[0077] The IrRu oxide catalyst 1 prepared in Example 1 was subjected to an LSV test.

[0078] IrRu oxide catalyst 1 was treated in 0.5 mol / L sulfuric acid at 80°C for 30 min, then filtered, washed, and dried. 2 mg of the treated IrRu oxide catalyst 1 and 0.2 mg of conductive carbon black were taken, and then 100 μL of deionized water, 100 μL of ethanol, and 10 μL of 5% Nafion solution were added. The mixture was ultrasonically treated in an ultrasonic bath for 1 h to form a uniform catalyst dispersion. Subsequently, 5 μL of the catalyst dispersion was dispersed and dripped onto a glassy carbon electrode with a diameter of 3 mm, and used for LSV testing after natural drying.

[0079] In the LSV test, the electrolyte is sulfuric acid with a concentration of 0.5 mol / L, the counter electrode is a platinum sheet electrode or a platinum mesh electrode, the reference electrode is an Ag / AgCl electrode, the scanning range is 1~1.8V vs NHE, the scanning speed is 5mV / s, and the LSV is scanned cyclically until the curves overlap.

[0080] Comparative Example 1:

[0081] The preparation method is substantially the same as that of Example 1, except that the solution environment is adjusted to a neutral condition, 1.6 g of polyether F188 is replaced by 1.6 g of sodium dodecyl sulfate, which is a typical ionic surfactant, to prepare IrRu oxide catalyst 1'.

[0082] The performance of the IrRu oxide catalyst 1' prepared in this comparative example 1 was tested. At the same current density as in Example 1, the IrRu oxide catalyst 1' had a current density of 10 mA / cm 2 The lower overpotential is 369 mV, indicating that the IrRu oxide catalyst 1 prepared by non-ionic surfactant has better performance.

[0083] The IrRu oxide catalyst 1 prepared in Example 1 was subjected to CV test and proton exchange membrane electrode test.

[0084] CV test process: 5 mg of IrRu oxide catalyst 1 prepared in Example 1 was taken, and then 170 μL of deionized water, 300 μL of isopropanol, and 30 μL of 5% Nafion solution were added, and ultrasonic treatment was performed in an ultrasonic bath for half an hour to form a uniform catalyst dispersion. Subsequently, 25 μL of the catalyst dispersion was dispersed and dripped on an active area of ​​0.5×0.5 cm 2 The platinum-coated titanium felt loaded with catalyst was dried in a forced air drying oven at 80°C for 3 h and then used for CV test.

[0085] In the CV test, the electrolyte is 0.5 mol / L sulfuric acid, the counter electrode is a platinum sheet electrode or a platinum mesh electrode, the reference electrode is an Ag / AgCl electrode, the scanning range is 0.95~1.75V, the scanning speed is 50mV / s, and the number of scanning circles is 5000. Before the test, it is necessary to scan 100 circles at a voltage of 1~1.7V and a scanning speed of 100mV / s to stabilize the catalyst.

[0086] Figure 5 The CV stability curve of the IrRu oxide catalyst 1 prepared in Example 1 of the present invention is shown. Figure 5 As shown, it can be seen that after 5000 CV cycles, the current of IrRu oxide catalyst 1 at a potential of 1.75 V only decays by 10%, indicating that IrRu oxide catalyst 1 has good stability during the application process.

[0087] Embodiment 2:

[0088] 1.6 g of nonionic surfactant polyether F188 was dissolved in 30 mL of water and stirred for 0.5 h to form a solution.

[0089] Then, 2.4 mL of concentrated hydrochloric acid and 1.4 mL of glacial acetic acid were added to the solution and stirred evenly, and 0.4 mmol of IrCl3·3H2O was added and stirred evenly to allow the iridium salt precursor to be adsorbed onto the F188 micelles.

[0090] The formed solution was placed in an oven at 50°C and slowly dried until a gel was obtained, and the obtained gel was calcined in air at 500°C for 4 h to prepare Ir oxide catalyst 2. Its overpotential in the LSV test was 343 mV.

[0091] Embodiment 3:

[0092] 1.6 g of nonionic surfactant polyether F188 was dissolved in 30 mL of water and stirred for 0.5 h to form a solution.

[0093] Then, 2.4 mL of concentrated hydrochloric acid and 1.4 mL of glacial acetic acid were added to the solution and stirred evenly, and 0.4 mmol of RuCl3·3H2O was added and stirred evenly to allow the ruthenium salt precursor to be adsorbed onto the F188 micelles.

[0094] The formed solution was placed in an oven at 50°C and slowly dried until a gel was obtained, and the obtained gel was calcined in air at 500°C for 4 hours to prepare Ru oxide catalyst 3. Its overpotential in the LSV test was 261 mV.

[0095] Embodiment 4:

[0096] 1.6 g of nonionic surfactant polyether F188 was dissolved in 30 mL of water and stirred for 0.5 h to form a solution.

[0097] Then, 2.4 mL of concentrated hydrochloric acid and 1.4 mL of glacial acetic acid were added to the solution and stirred evenly, and 15 mg of RuCl3·3H2O, 15 mg of IrCl3·3H2O, 15 mg of HAuCl4 and 15 mg of platinum acetylacetonate were added and stirred evenly to allow the ruthenium salt precursor to be adsorbed onto the F188 micelles.

[0098] The formed solution was placed in an oven at 50°C and slowly dried until a gel was obtained, and the obtained gel was calcined in air at 500°C for 4 hours to prepare IrRuPtAu composite oxide catalyst 4. Its overpotential in the LSV test was 295 mV.

[0099] Embodiment 5:

[0100] The steps are the same as those in Example 1, except that the calcination temperature is 600° C. and the calcination time is 4 h, and the obtained catalyst is IrRu oxide catalyst 5. Its overpotential in the LSV test is 223 mV.

[0101] Figure 6 The linear voltammetric scanning (LSV) histograms after iR compensation of the oxide catalysts prepared in Examples 1 to 5 of the present invention and the IrRu oxide catalyst 1' prepared in Comparative Example 1 are shown. Figure 6 As shown, it can be seen that the IrRu oxide catalyst 1 in Example 1 is 2 The overpotential is only 247 mV. The IrRu oxide catalyst 5 in Example 5 has a 2 The lower overpotential is only 223 mV, and the overpotentials of Examples 2 to 4 are all lower than that of Comparative Example 1, indicating that Examples 1 to 5 have better electrocatalytic oxygen evolution performance than Comparative Example 1.

[0102] Embodiment 6:

[0103] 2 g of nonionic surfactant polyether F127 was dissolved in 30 mL of water and stirred for 0.5 h to form a solution.

[0104] Then, 4 mL of concentrated hydrochloric acid and 1 mL of glacial acetic acid were added to the solution and stirred evenly, and 0.2 mmol of IrCl3 and 0.2 mmol of RuCl3 were added and stirred evenly to allow the metal precursor to be adsorbed onto the F127 micelles.

[0105] The formed solution was placed in an oven at 30°C and slowly dried until a gel was obtained. The obtained gel was calcined in air at 200°C for 10 h to prepare IrRu oxide catalyst 6.

[0106] Embodiment 7:

[0107] 0.5 g of nonionic surfactant PEO-b-PS was dissolved in 30 mL of water and stirred for 0.5 h to form a solution.

[0108] Then, 0.5 mL of concentrated hydrochloric acid and 4 mL of glacial acetic acid were added to the solution and stirred evenly, and 0.1 mmol of H2IrCl6·6H2O and 0.3 mmol of K2RuCl6 were added and stirred evenly to allow the metal precursor to be adsorbed onto the PEO-b-PS micelles.

[0109] The formed solution was placed in an oven at 80°C and slowly dried until a gel was obtained. The obtained gel was calcined in air at 800°C for 0.5 h to prepare IrRu oxide catalyst 7.

[0110] Embodiment 8:

[0111] 0.5 g of nonionic surfactant polyether F123 was dissolved in 30 mL of water and stirred for 0.5 h to form a solution.

[0112] Then, 4 mL of concentrated hydrochloric acid and 0.5 mL of glacial acetic acid were added to the solution and stirred evenly, and 0.05 mmol of K2IrCl6 and 10 mmol of ruthenium acetylacetonate were added and stirred evenly to allow the metal precursor to be adsorbed onto the F123 micelles.

[0113] The formed solution was placed in an oven at 70°C and slowly dried until a gel was obtained. The obtained gel was calcined in air at 700°C for 1 h to prepare IrRu oxide catalyst 8.

[0114] Embodiment 9:

[0115] 0.5 g of nonionic surfactant polyether F124 was dissolved in 30 mL of water and stirred for 0.5 h to form a solution.

[0116] Then, 2 mL of concentrated hydrochloric acid and 2 mL of glacial acetic acid were added to the solution and stirred evenly, and 10 mmol of K2IrCl6 and 0.05 mmol of ruthenium acetylacetonate were added and stirred evenly to allow the metal precursor to be adsorbed onto the F124 micelles.

[0117] The formed solution was placed in an oven at 90° C. and slowly dried until a gel was obtained. The obtained gel was calcined in air at 700° C. for 4 h to prepare IrRu oxide catalyst 9.

[0118] Embodiment 10:

[0119] The method is the same as that of Example 1, except that the non-ionic surfactant used is polyether L65, the Ir precursor is iridium tetrachloride, and the Ru precursor is ammonium chlororuthenate, to prepare the IrRu oxide catalyst 10.

[0120] Embodiment 11:

[0121] The method is the same as that of Example 2, except that the non-ionic surfactant used is polyether F68, the Ir precursor is iridium tetrachloride, and the Ru precursor is sodium chlororuthenate, to prepare IrRu oxide catalyst 11.

[0122] Embodiment 12:

[0123] The method is the same as that in Example 3, except that the nonionic surfactant used is poly(propylene glycol)-block-poly(ethylene glycol)-block-poly(propylene glycol), and the Ir precursor is iridium acetate, to prepare IrRu oxide catalyst 12.

[0124] Embodiment 13:

[0125] The method is the same as that in Example 3, except that the nonionic surfactant used is poly(propylene glycol)-block-poly(ethylene glycol)-block-poly(propylene glycol), and the Ir precursor is chloroiridic acid, to prepare IrRu oxide catalyst 13.

[0126] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A porous IrRu oxide catalyst for catalytic application in biomass oxidation reaction and water electrolysis oxygen evolution reaction, characterized in that: The porous IrRu oxide catalyst is prepared by the following method: Adding an iridium salt precursor and a ruthenium salt precursor to an acidic solution containing a nonionic surfactant and stirring the solution to obtain a mixed solution, wherein the iridium ions and the ruthenium ions are adsorbed onto micelles formed by the nonionic surfactant; Drying the mixed solution to obtain a gel adsorbing iridium ions and ruthenium ions, wherein the drying temperature is 20-90° C.; The gel adsorbed with iridium ions and ruthenium ions is calcined in air to prepare the porous IrRu oxide catalyst, wherein the calcination conditions are: heating to 500-800° C. at a heating rate of 1-20° C. / min, and calcining at a heat treatment temperature of 500-800° C. for 0.5-10 h; The nonionic surfactant is selected from any one or more of polyether F68, polyether F123, polyether F124, polyether F188, polyether L65, polyethylene glycol-b-polystyrene, poly(propylene glycol)-block-poly(ethylene glycol)-block-poly(propylene glycol), fatty alcohol polyoxyethylene ether, fatty acid polyoxyethylene ester, octadecylamine polyoxyethylene ether, and polyoxyethylene fatty amide 704; The acidic solution containing the nonionic surfactant is prepared by the following operation: Dissolving a nonionic surfactant in water and stirring to obtain a solution containing the nonionic surfactant; adding an acid to the solution to form an acidic solution containing a nonionic surfactant; Wherein, the acid is a combination of concentrated hydrochloric acid and glacial acetic acid.

2. The catalytic application according to claim 1, characterized in that: The iridium salt precursor includes at least one of iridium tetrachloride, iridium trichloride or its hydrate, chloroiridic acid or its hydrate, iridium acetate, ammonium chloroiridate, potassium chloroiridate, sodium chloroiridate, potassium bromoiridate, sodium bromoiridate, tricarbonyl iridium chloride, dodecacarbonyl tetrairidium, and iridium iodide; The ruthenium salt precursor includes: at least one of ruthenium trichloride or its hydrate, ammonium chlororuthenate, potassium chlororuthenate, sodium chlororuthenate, ruthenium acetylacetonate, ruthenium acetate, ruthenium acetate, ruthenium bromide, ruthenium iodide, potassium perruthenate, hexacarbonyl ruthenium chloride, dodecacarbonyl triruthenium, ruthenium red tetrahydrate, and ruthenium nitrosyl acetate; Other precious metal precursors are optionally added during the preparation process, including at least one of chloroplatinic acid, ammonium chloroplatinate, platinum dichloride, platinum sulfite, platinum tetrachloride, potassium chloroplatinate, potassium chloroplatinite, lithium chloroplatinate hydrate, sodium chloroplatinite, sodium chloroplatinate, potassium platinum hexabromide, chloroauric acid, potassium gold chloride, sodium chloroaurate, palladium chloride, sodium chloropalladate, ammonium chloropalladate, palladium nitrate, palladium sulfate, palladium propionate, potassium bromopalladate, potassium chloropalladate, palladium acetate, sodium hexachloropalladate, rhodium chloride, potassium chlororhodate, ammonium chlororhodate, rhodium nitrate, rhodium sulfate, and rhodium acetate.

3. The catalytic application according to claim 1, characterized in that: In the porous IrRu oxide catalyst, the weight percentage of iridium is 1-100%.

Citation Information

Patent Citations

  • Porous oxide catalyst and method of preparing the porous oxide catalyst

    US20110230337A1